Survey of secondary school students’ attitude towards agricultural science (2014)
This study surveys the attitude of Secondary School Students towards Agricultural Science in Oke-Ogun Area of Oyo State. Sample sire of 240 respondents was chosen through simple random sampling technique. Interview schedule and structured questionnaire were also used in data collection. Major findings showed that the majority of the students were in the age group of 16 - 18 years. Males and females of the respondents were of equal percentages. The findings revealed that male students had a more positive attitude towards agriculture as a career than their female counterparts. About 57.5% were influenced by their parents on career decision. The result also showed that male students had favourable attitude towards agriculture as a career (85%) than their female student's counterparts of12.5%. There is a positive significant relationship between the parents' socio-economic background and the students' attitude towards agriculture. The study, thus, recommends that the government should put in place appropriate machineries so that students would have favourable attitudes toward agriculture thereby increasing the likelihood of students making career in Agricultural science